2016
DOI: 10.1016/j.foodchem.2016.03.112
|View full text |Cite
|
Sign up to set email alerts
|

Regional features of northern Italian sparkling wines, identified using solid-phase micro extraction and comprehensive two-dimensional gas chromatography coupled with time-of-flight mass spectrometry

Abstract: We carried out comprehensive mapping of volatile compounds in 70 wines, from 48 wineries and 6 vintages, representative of the two main production areas for Italian sparkling wines, by HS-SPME-GCxGC-TOF-MS and multivariate analysis. The final scope was to describe the metabolomics space of these wines, and to verify whether the grape cultivar signature, the pedoclimatic influence of the production area, and the complex technology were measurable in the final product. The wine chromatograms provided a wealth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 38 publications
3
49
0
2
Order By: Relevance
“…By the use of chemometric analysis, diethyl malonate was pointed out as one of the most important compounds having strong influence in the Chardonnay wines differentiation [ 33 ]. In the work by Carlin et al [ 34 ], the above mentioned compounds were also reported with concentrations of diethyl glutarate (5.8–7.3 µg L −1 ) similar to our data (12.0–19.9 µg L −1 ). Sparkling wines from Krašić stood out with significantly the highest concentration of diethyl malonate, while there was no significant difference in diethyl glutarate concentrations among tested wines.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…By the use of chemometric analysis, diethyl malonate was pointed out as one of the most important compounds having strong influence in the Chardonnay wines differentiation [ 33 ]. In the work by Carlin et al [ 34 ], the above mentioned compounds were also reported with concentrations of diethyl glutarate (5.8–7.3 µg L −1 ) similar to our data (12.0–19.9 µg L −1 ). Sparkling wines from Krašić stood out with significantly the highest concentration of diethyl malonate, while there was no significant difference in diethyl glutarate concentrations among tested wines.…”
Section: Resultssupporting
confidence: 92%
“…Also, according to Marais et al [ 38 ], the TDN levels were remarkably higher in grapes that had more sunlight during maturation than in grapes from shaded locations. So, there is a reason to point out a potential impact of pruning level as well as leaf removal on carotenoid levels [ 34 ]. In the work by Francioli et al [ 7 ], TDN was pointed out as a compound that, together with diethyl succinate and vitispirane, can discriminate cavas aged >20 months.…”
Section: Resultsmentioning
confidence: 99%
“…The aroma is one of the most important compound linked to wine quality, influencing its typicality and acceptability. The aromatic profile of sparkling wines from traditional method is associated to volatile compounds belonging to esters, alcohols, acids, and some terpenes, in a very complex matrix [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics enabled the determination of the crops metabolome (phenotyping ) by differentiating the composition of low molecular weight compounds in soybean , rice and beans cultivars (Mensack et al, 2010), subsequently enabled the differentiation of regional products in terms of their origin (Zieliński et al, 2014) or the impact of stressors on living organisms (Dita et al, 2006). Metabolomics methods make it possible to create a distinctive set of metabolites -attributed to specific regional productswhich determine their originality and quality (Carlin et al, 2016). The evaluation and characterization of crops in terms of the composition of metabolites may enable quality control of final products in the food industry by changing storage conditions (Arapitsas et al, 2016) and potentially allowing to plan crops by knowing influence of environmental condition in order to achieve a higher quality by special composition of metabolome (Fernie and Schauer, 2009).…”
Section: Metabolomicsmentioning
confidence: 99%